Evaluation of ISO 9001 lead auditor training program using CIPP model at ATS training centre - Kifta, Decky Antony; Ambiyar, Ambiyar; Rizal, Fahmi; Islami, Syaiful (Jurnal Pendidikan Teknologi Kejuruan, 2022)
This research is performed to evaluate the implementation of ISO 900A Lead Auditor Training program using CIPP model evaluation method which comprising of four aspects i.e.: (1) Context, (2) Input, (3) Process and (4) Product. The research method is using mixed method by using both quantitative and qualitative methods, where the data are collected using sampling technique by distributing questionnaires to 15 trainers and 25 trainees or training participants. The data also enriched by using qualitative method of interview and observation done on trainers and training participants. The results of the research and studies show that the training program from the context aspects of the trainers is 80.65% and from participants is 80.45%, from the input aspects of the trainers and participants are consecutively 81.5% and 75.87%, from the process aspects are 79.2% and 71.87%, and from the product aspects of trainers and participants are 80.02% and 75.7%. This can be concluded that the range of TPR are from 71.87% to 81.5% which fall into ‘good’ and ‘very good’ categories.